PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP LUAS PENGUNGKAPAN TANGGUNG JAWAB SOSIAL - Devi Widya Astuti (AKUNTANSI DEWANTARA, 2019)
This research is aimed to at knowing the effect of profitability, leverage, and company size to corporate sosial responsibility disclosure of mining companies. The population in this study were mining companies listed on the Indonesian stock exchange. The samples in this study are 11 companies. The data used is secondary data from www.idx.co.id. Data analysis techniques used multiple linear regression analysis and a measurement instruments to test this research use SPSS. The affect of three variable are profitability, leverage and company size of corporate sosial responsibility disclosure 35,2%, while the rest is influenced by other factors outside research variable. Partially, profitability has a significant positive effect on CSR with significance value 0,002<0,05, leverage has no significant effect on CSR with significance value 0,106>0,05, Company size has significant on CSR with significance value 0,001<0,05.